2000
DOI: 10.1093/gerona/55.6.b286
|View full text |Cite
|
Sign up to set email alerts
|

Low Fatty Acid Unsaturation: A Mechanism for Lowered Lipoperoxidative Modification of Tissue Proteins in Mammalian Species With Long Life Spans

Abstract: Carbonyl compounds generated by the nonenzymatic oxidation of polyunsaturated fatty acids react with nucleophilic groups in proteins, leading to their modification. It has not been tested whether fatty acid unsaturation is related to steady-state levels of lipoxidation-derived protein modification in vivo. A low fatty acid unsaturation, hence a low protein lipoxidation, in tissues of longevous animals would be consistent with the free radical theory of aging, because membrane lipids increase their sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
1
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 34 publications
6
36
1
3
Order By: Relevance
“…Thus the novel and unexpected finding that the composition of membrane bilayers varies systematically in mammals provided a link between metabolic rate and maximum life span of mammalian species. In agreement with this, it was demonstrated that in long-lived mammals, the low degree of membrane fatty acid unsaturation was accompanied by a low sensitivity to in vivo and in vitro lipid peroxidation (269,272,(275)(276)(277) and a low steady-state level of lipoxidation-derived adducts in both tissue and mitochondrial proteins of skeletal muscle, heart, liver, and brain (267,268,274,277,292,307). These findings were consistent with the negative correlation between MLSP and the sensitivity to lipid autoxidation of mammalian kidney and brain homogenates that had been described some years earlier (72).…”
Section: Membrane Composition Lipid Peroxidation Body Size and supporting
confidence: 66%
“…Thus the novel and unexpected finding that the composition of membrane bilayers varies systematically in mammals provided a link between metabolic rate and maximum life span of mammalian species. In agreement with this, it was demonstrated that in long-lived mammals, the low degree of membrane fatty acid unsaturation was accompanied by a low sensitivity to in vivo and in vitro lipid peroxidation (269,272,(275)(276)(277) and a low steady-state level of lipoxidation-derived adducts in both tissue and mitochondrial proteins of skeletal muscle, heart, liver, and brain (267,268,274,277,292,307). These findings were consistent with the negative correlation between MLSP and the sensitivity to lipid autoxidation of mammalian kidney and brain homogenates that had been described some years earlier (72).…”
Section: Membrane Composition Lipid Peroxidation Body Size and supporting
confidence: 66%
“…In this case, lower levels were observed in the brain of both parakeets and canaries compared to mice. Similarly, in every previous study performed to date, MDAL protein levels were always relatively lower in long-lived species, regardless of whether they were birds or mammals (Pamplona et al 1999(Pamplona et al , 2000Portero-Otin et al 2004;Ruiz et al 2005). MDAL is formed by covalent attachment of aldehydic functions of malondialdehyde (an important lipid peroxidation product) to lysine protein residues.…”
Section: Discussionmentioning
confidence: 74%
“…Although we have not measured ROS, it may be appropriate to mention that in vitro stimulation by iron and H 2 O 2 in the young and old animals result in an age-related decrease in the magnitude of response, which are correlated to alterations in the fatty acid composition during aging. An increase in MDA synthesis following iron and peroxide stimulation has been reported in aged mice [13,28]. Adult mice have better capacity to buffer exogenous stimuli and in contrast to aged mice, which are no longer able to counteract the enhanced production of MDA.…”
Section: Discussionmentioning
confidence: 99%